Long-term nitric oxide exposure induces cough hypersensitivity via non-inflammatory activation of the HIF1α–TRPV1 pathway - Zhao, Jingxin; Jiang, Jinjun; Zhang, Peifang; Xiong, Yue; Yan, Rong; Zhang, Chuling; Zeng, Xuan; Deng, Wenbin; Nie, Yichu (Frontiers in Pharmacology, 2026)
BackgroundChronic cough hypersensitivity is common across respiratory diseases and often occurs without airway inflammation, yet effective treatments remain limited. Nitric oxide (NO), an important endogenous signaling molecule and environmental pollutant, has been implicated in respiratory pathophysiology, but its role in cough hypersensitivity remains unclear.AimThe aim of this study was to investigate whether long-term NO exposure induces cough hypersensitivity and to define the underlying mechanisms involved.MethodsA guinea pig model of chronic NO exposure was established and compared with a cigarette smoke (CS) –induced cough model. Cough sensitivity was assessed using capsaicin challenge tests. Airway pathology and inflammation were evaluated by histological staining and molecular analyses in vivo and in 16HBE epithelial cells. Expression of TRPV1 and HIF1α was examined in tracheal tissues and ND7/23 sensory neuron-like cells using immunofluorescence and qPCR.ResultsAcute NO exposure did not trigger coughing. Notably, prolonged NO exposure significantly increased capsaicin-induced cough frequency and reduced cough latency. In contrast to CS, chronic NO exposure did not induce airway inflammation, epithelial remodeling, or cytokine upregulation. Instead, NO exposure markedly enhanced the expression of TRPV1 and HIF1α in airway sensory fibers and ND7/23 cells.ConclusionThese findings demonstrate that prolonged NO exposure induces cough hypersensitivity via HIF1α–TRPV1–mediated neural sensitization, independent of airway inflammation. This study establishes a novel non-inflammatory model of chronic cough and identifies potential therapeutic targets for refractory cough.